Determination of the influence of liquid molecule structure on acoustic absorption quantity - LINDE, Bogumił; KOSMOL, Marek; ŚLIWIŃSKI, Antoni (Archives of Acoustics, 1986)
This paper is concerned with the propagation mechanism of ultrasonic waves. It was aimed at the determination of relation the values of the absorption coefficient (a /f^2)_rel and the structure of liquid molecules. Such relation were observed in the course of investigations performed on cyclic compounds [1-4].